Some Aspects of Fiscal and Monetary Tools of the Environmental Sustainability – Through the Case of Hungary - Lentner, Csaba; Zsarnóczai, Sándor J. (Public Governance, Administration and Finances Law Review, 2022)
On the one hand, economic sustainability depends on an environmentally friendly and energy-saving economy, though it rather means the continuous functioning of businesses and the national economy, which is expressed in the balance of accounting, foreign trade and budget balances. On the regulatory side, monetary policy, alongside fiscal policy, serves ensuring economic sustainability, as the main objective of central banks is to ensure price stability and maintain financial equilibrium to underpin continued economic activity. However, in our energy crisis-ridden world, there is an increasing emphasis on energy-efficient, environmentally friendly management. The focus of our study is on the environmental sustainability context of Hungarian fiscal and central bank tools, with a particular focus on the legislative and programmatic elements of the green economy development of the Magyar Nemzeti Bank (Hungarian National Bank, hereinafter: MNB).